2021
DOI: 10.1093/ofid/ofab252
|View full text |Cite
|
Sign up to set email alerts
|

Cefiderocol Pharmacokinetics in a Patient Receiving Continuous Venovenous Hemodiafiltration

Abstract: Antimicrobial dosing in patients receiving continuous renal replacement therapy (CRRT) are a continued clinical challenge. We describe a case of a patient receiving cefiderocol 2 g IV every 8 hours as a 3 hour infusion for a multi-drug resistant Pseudomonas aeruginosa pneumonia and bacteremia while undergoing CVVHDF. The clinical course and cefiderocol pharmacokinetics are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Twenty-five studies investigated the characteristics of PK and/or PD of cefiderocol ( Katsube et al, 2016 ; Katsube et al, 2017 ; Matsumoto et al, 2017 ; Monogue et al, 2017 ; Ghazi et al, 2018a ; Ghazi et al, 2018b ; Katsube et al, 2018 ; Kawaguchi et al, 2018 ; Saisho et al, 2018 ; Katsube et al, 2019a ; Kidd et al, 2019a ; Katsube et al, 2019b ; Kidd et al, 2019b ; Chen et al, 2019 ; Miyazaki et al, 2019 ; Nakamura et al, 2019 ; Stainton et al, 2019 ; Matsumoto et al, 2020 ; Ota et al, 2020 ; Gill et al, 2021 ; Katsube et al, 2021 ; Kawaguchi et al, 2021 ; Kobic et al, 2021 ; König et al, 2021 ; Nakamura et al, 2021 ). A phase I study including healthy Japanese and Caucasian volunteers showed exhibit linear PK at doses of up to 2,000 mg, with low to moderate interindividual variability ( Saisho et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five studies investigated the characteristics of PK and/or PD of cefiderocol ( Katsube et al, 2016 ; Katsube et al, 2017 ; Matsumoto et al, 2017 ; Monogue et al, 2017 ; Ghazi et al, 2018a ; Ghazi et al, 2018b ; Katsube et al, 2018 ; Kawaguchi et al, 2018 ; Saisho et al, 2018 ; Katsube et al, 2019a ; Kidd et al, 2019a ; Katsube et al, 2019b ; Kidd et al, 2019b ; Chen et al, 2019 ; Miyazaki et al, 2019 ; Nakamura et al, 2019 ; Stainton et al, 2019 ; Matsumoto et al, 2020 ; Ota et al, 2020 ; Gill et al, 2021 ; Katsube et al, 2021 ; Kawaguchi et al, 2021 ; Kobic et al, 2021 ; König et al, 2021 ; Nakamura et al, 2021 ). A phase I study including healthy Japanese and Caucasian volunteers showed exhibit linear PK at doses of up to 2,000 mg, with low to moderate interindividual variability ( Saisho et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cefiderocol was mainly eliminated unchanged in urine ( Miyazaki et al, 2019 ), with metabolism contributing to less than 10% elimination ( Saisho et al, 2018 ). Since cefiderocol is primarily eliminated through the renal route, renal impairment alters area under the plasma concentration-time curve (AUC), total drug clearance from plasma (CL) and terminal half-life (t 1/2 ), without significantly affecting the maximum plasma concentration (C max ) ( Katsube et al, 2017 ; Kawaguchi et al, 2018 ; Kobic et al, 2021 ; König et al, 2021 ). Kawaguchi, et al evaluated the PK of cefiderocol in patients with pneumonia, bloodstream infection/sepsis, or complicated urinary tract infection, finding that no other factors, including infection sites and mechanical ventilation, were statistically significant covariates in the population PK analysis ( Kawaguchi et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, there is limited clinical data for cefiderocol PK in patients undergoing CVVH [ 9 , 10 , 11 ]. In this case series, we provide data on the PK of cefiderocol as salvage therapy in three critically ill patients on CVVH and cytokine absorbers while affected by severe DTR-AB infections with limited treatment options ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetic cefiderocol was recently evaluated in patients with renal dysfunction, but dosing in patients receiving CVVH is mainly extrapolated from cefepime pharmacokinetics (PK) because of the similarity in molecular weights and protein binding between cefepime and cefiderocol [ 9 , 10 , 11 ]. Here, we report for the first time the pharmacokinetic cefiderocol in three critically ill patients undergoing CVVH with severe infections due to DTR-AB.…”
Section: Introductionmentioning
confidence: 99%
“…Although detailed dosing recommendations in patients with CRRT are enclosed in its package insert, very few real-world published data exist. We previously described cefiderocol PK in a patient with Pseudomonas aeruginosa pneumonia and bacteremia undergoing CVVHDF [ 25 ]. Another report by Fratoni and colleagues described cefiderocol PK in a patient with Stenotrophomonas maltophilia undergoing CVVHDF [ 26 ].…”
Section: Discussionmentioning
confidence: 99%